Liberia : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
The 2012 Article IV Consultation with Liberia discusses the economic developments and policies of the country. Liberia recorded strong macroeconomic performance under the three-year Extended Credit Facility (ECF) Arrangement, but poverty continued to be pervasive. The short- to medium-term outlook has remained favorable, although subject to considerable risks. Following resumption of iron ore exports in 2011, real GDP growth is estimated at 9 percent in 2012, supported by strong growth in the mining sector and expansionary fiscal policy for infrastructure investment. IMF staff supports the authorities' request for a successor arrangement under the ECF.